A Short and Scalable Total Synthesis of (±)-β-Eudesmol - Panigrahi, Ashutosh; Bathigowda, Pratik; Prahlad P; Pulukuri, Kiran Kumar (Synlett, 2025)
A concise, protecting group-free approach has been developed for the total synthesis of (±)-β-eudesmol (1), completed in four steps with an overall yield of 24%. This synthesis features a copper-catalyzed Michael addition followed by an in situ aldol reaction, and a one-step Fe(III)/Et3SiH-mediated radical cyclization–oxidation sequence that efficiently constructs the eudesmane skeleton. With its operational simplicity and scalability, this strategy provides a valuable platform for the synthesis of structurally related sesquiterpenoid architectures, paving the way for further biological and structural investigations.
Keywords: Terpenoids; Michael addition; Aldol reaction; Oxidative cyclization; Natural product total synthesis